Implikasi Motivasi Kerja dan Kedisiplinan Terhadap Kinerja Pegawai Melalui Produktivitas Kerja Pada PT Pos Indonesia(Persero) Bekasi 17000 - Muhammad Ivan Susanto; Asrul; Andi Muhammad Sadli (Sekolah Tinggi Ilmu Ekonomi Mulia Pratama, 2023)
This research is a quantitative study that aims to determine the effect of work motivation and discipline on employee performance through work productivity at PT Pos Indonesia (Persero) Bekasi 17000. The population in this study are all employees at the head office of PT Pos Indonesia (Persero) Bekasi 17000.yang amounted to 48 people, while the determination of the sample is based on the saturated sample technique. The data analysis method used in this research is path analysis. The results of the study show that (1) work motivation has an effect on work productivity at PT Pos Indonesia (Persero) Bekasi 17000. (2) discipline has an effect on work productivity at PT Pos Indonesia (Persero) Bekasi 17000. (3) work motivation has an effect on employee performance At PT Pos Indonesia (Persero) Bekasi 17000. (4) Discipline affects employee performance at PT Pos Indonesia (Persero) Bekasi 17000. (5) Work productivity affects employee performance at PT Pos Indonesia (Persero) Bekasi 17000. (6) Work motivation affects employee performance through productivity at PT Pos Indonesia (Persero) Bekasi 17000. (7) Discipline affects employee performance through work productivity at PT Pos Indonesia (Persero) Bekasi 17000.